Nonlinear waves in disordered chains: probing the limits of chaos and spreading. - Bodyfelt JD; Laptyeva TV; Skokos C; Krimer DO; Flach S (AMER PHYSICAL SOC, 2011)
We probe the limits of nonlinear wave spreading in disordered chains which are known to localize linear waves. We particularly extend recent studies on the regimes of strong and weak chaos during subdiffusive spreading of wave packets [Europhys. Lett. 91, 30001 (2010)] and consider strong disorder, which favors Anderson localization. We probe the limit of infinite disorder strength and study Fröhlich-Spencer-Wayne models. We find that the assumption of chaotic wave packet dynamics and its impact on spreading is in accord with all studied cases. Spreading appears to be asymptotic, without any observable slowing down. We also consider chains with spatially inhomogeneous nonlinearity, which give further support to our findings and conclusions.
Keywords: Science & Technology; Physical Sciences; Physics, Fluids & Plasmas; Physics, Mathematical; Physics; PHYSICS, FLUIDS & PLASMAS; PHYSICS, MATHEMATICAL; ANDERSON LOCALIZATION; TRANSPORT; LATTICES; SYSTEMS; MODEL; 01 Mathematical Sciences; 02 Physical Sciences; 09 Engineering